DETEKSI EKTOPARASIT DAN ENDOPARASIT PADA KUCING PELIHARAAN (FELIS DOMESTICUS) DI WILAYAH TAMBAKSARI, SURABAYA - Vella Rohmayani; Dita Artanti; Ruspeni Daesusi; Anindita Riesti Retno Arimurti (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Domestic Cats (Felis domesticus) are favorite mammals that are mostly kept by humans. One of the obstacles in keeping cats is that they can be infected with ectoparasites and endoparasites. Many ectoparasite and endoparasite infections are zoonotic, so the cat's hygiene and health must be maintained by the owner. This study aims to determine the presence of ectoparasite and endoparasite infections in domestic cats in the Tambaksari area of Surabaya.The sample in this study were 32 cats that were kept in the Tambaksari area, Surabaya. This research was conducted on 32 domestic cats in the Tambaksari area of Surabaya. The examination was divided into 2, namely the examination of ectoparsites by means of which were carried out on the body surface, starting from the head, body, legs, and tail. While the examination of endoparasites by means of examination of feces by flotation method using saturated NaCl. The results of the examination were 21.87% positive for infection by ectoparasites, 78.12% were not infected with ectoparasites. The types of ectoparasites that infect are the Felicola subrostarus and the Ctenocephalides felis. While the results of endoparasite examination, as many as 9.37% were positively infected by endoparasites, 90.63% were not infected with endoparasites. Types of endoparasites found eggs of Toxocara spp. and Ancylostoma spp. So ectoparasites and endoparasites infections in domestic cats in the Tambaksari area of Surabaya are quite low. Cat owners should pay more attention to the cleanliness and health of their domestic cats Keyword: Ectoparasite, Endoparasite, Cat, Felicola subrostarus, Ctenocephalides felis, Toxocara spp., Ancylostoma spp.